Exploring the possibility of developing an effective solid waste management practices for two towns in Sarawak :an action research study - Bujang, Bin Hj. Budin (1998)
The study on solid waste management focuses on the need to have a clean environment for Lundu and Sematan towns. Both towns were found to be dirty due the fact that rubbish and garbage were not disposed properly. The lack of facilities such as garbage bins coupled with a poor solid waste management system practiced by Lundu District Council had caused both towns to be in an unkempt condition. In conducting this study, the researcher and five other senior members of the council formed an action research group. The main objectives of this group were to identify ways to solve the impending problems of poor solid waste management, to identify workable practices that could help in improving the condition of both towns, to identify new learning practices on solid waste management among the group members that could be transferred and used at the workplace and finally to work as a team in solving problems and making decision pertaining to solid waste management.